A novel electrochemical assay for aspartame determination via nucleophilic reactions with caffeic acid ortho-quinone - Lê, Vũ Trâm Anh (Elsevier, 2022)
Cyclic voltammetry (CV) in a pH 7.0 phosphate buffer solution containing aspartame (ASP) and caffeic acid (CAF) was studied. In sharp contrast to untreated electrodes, two distinct redox peaks were observed at preanodized screen-printed carbon electrodes (SPCE*) due to the formation of a homopolymer poly(CAF) and a copolymer poly(CAF-ASP). The characteristics of the polymer film-modified electrodes were well-characterized by atomic force microscopy (AFM), photoelectron spectroscopy (XPS) and the water contact angle technique. Electrochemically induced polymerization mechanisms were discussed. Current responses from poly(CAF-ASP) were employed for ASP determination, and a linear dynamic range from 0.05 µM to 10 μM was obtained using differential pulse voltammetry (DPV). The detection limit (S/N = 3) was 0.0076 µM, the quantitation limit (S/N=10) was 0.0256 µM and the sensitivity was 12.067 μA μM-1. Common additives in soft drinks do not interfere with the ASP analysis. The proposed assay and a reference high-performance liquid chromatography (HPLC) were applied for the determination of ASP in two soft drinks using the standard addition method, and satisfactory recoveries and good agreement were obtained.